Keberadaan Tungau Debu Rumah (TDR) di Permukiman Manusia - Mirnawati Dewi; Defilia Anogra Riani (Jurnal Rumpun Ilmu Kesehatan, 2024)
Mite is a species of arthropod of the class Arachnida, subclass Acari or Acarina, that lives in various habitats. House dust mites (TDRs) are the main source of allergens in house dust. The purpose of this study is to identify the existence and types of mites found in human dwellings. This study is an observational analysis carried out by taking samples of house dust in the house. Microscopic examination and identification were carried out in the FMIPA laboratory, UPR. The results of the study showed the presence of various types of mites, such as Dermatophagoides sp., Blomia tropicalis, Tyrophagus sp. Mite activity leads to a loss of sanitary quality. Inhalation, swallowing, or contact with mites, metabolic byproducts, and feces can cause susceptible individual sensitivities and cause asthma, allergic rhinitis, contact dermatitis, enteritis, and cause anaphylaxis. Monitoring the temperature and humidity in the home is essential for mite control, as well as better conservation and hygiene.